2023
DOI: 10.1039/d2tb02629e
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linkable star-hyperbranched unimolecular micelles for the enhancement of the anticancer activity of clotrimazole

Abstract: Clotrimazole, a hydrophobic drug routinely used in the treatment of vaginal candidiasis, also shows antitumor activity. However, its use in chemotherapy has been unsuccessful due to its low solubility in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Analyzing the IC 50 values contained in Table , it can be concluded that all systems (except for PBGE-PGGE_2_CLOT_a) retained the tumor cell selectivity characteristic for the free drug. , The cytotoxicity of drug-loaded copolymers was not correlated with the amount of the drug entrapped in the analyzed structures. Comparing the clotrimazole loading within the copolymer (Table ) with the IC 50 values (Table ), it can be concluded that systems with a low drug loading were the most effective, as previously observed for star-hyperbranched amphiphilic constructs, and this can be explained that the high clotrimazole content in the polymer structure hindered its release and immediate action.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing the IC 50 values contained in Table , it can be concluded that all systems (except for PBGE-PGGE_2_CLOT_a) retained the tumor cell selectivity characteristic for the free drug. , The cytotoxicity of drug-loaded copolymers was not correlated with the amount of the drug entrapped in the analyzed structures. Comparing the clotrimazole loading within the copolymer (Table ) with the IC 50 values (Table ), it can be concluded that systems with a low drug loading were the most effective, as previously observed for star-hyperbranched amphiphilic constructs, and this can be explained that the high clotrimazole content in the polymer structure hindered its release and immediate action.…”
Section: Resultsmentioning
confidence: 99%
“…A P(AM- ran -2-AAPBA) copolymer was obtained according to the procedure described previously 36 using AIBN (0.082 g; 0.5 mmol), acrylamide (4.68 g; 65.84 mmoL), and 2-acrylamidephenylboronic acid pinacol ester (2 g; 7.31 mmoL). The polymerization was carried out in 15 mL of a dimethylformamide (DMF)/dioxane mixture (5:1 v/v) at 70 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CLT was encapsulated within aryl-enriched HbPGL using a solvent evaporation method 23 using methanol as a good solvent for both drug and polymer. Among all investigated formulations, a molar ratio of drug/macromolecule equal to 32 was optimal to obtain uniform gel-like structured fluids for all HbPGL derivatives of significantly reduced flow properties.…”
Section: Resultsmentioning
confidence: 99%
“…The complete release of CLT from these hydrogel carriers was limited to several hours. Recently, a novel synthetic strategy of CLT-enriched hydrogels constructed of dynamic cross-links has been elaborated based on the usage of drug-loaded unimolecular micelles displaying prolonged CLT release reaching 40 h. This approach required, however, the use of a cross-linking agent for hydrogel formation.…”
Section: Introductionmentioning
confidence: 99%